DDoS detection mechanism using trust-based evaluation system in VANET - Poongodi, M. (2021)
It is essential for Vehicular Ad-hoc networks (VANETs) to have reliable vehicles for communication with vehicles. VANET is dynamical network where the vehicles frequently alter their place. Safe routing is of great essence at the time of routing process to fit in shared trust/belief involving these nodes. Occasionally, the malicious node transmits the counterfeit data amid other nodes. To find out trust/belief is deemed to be a difficult task when the malicious nodes try to distort the discovery of route or transmission of data within the network. Researchers have worked extensively to ensure a safe routing process with trust-oriented applications. We develop the framework based on trust with a fresh mechanism to determine DDoS attacks in VANET. The major trust elements in the evaluation of trust are frequency value statistics, trust hypothesis statistics, residual energy, trust policy, and data factor. Based on the trust elements, the generation of trust evaluation matrix takes place. We develop the suggested trust mechanism in an innovative manner to offer the security in a better manner by avoiding the trespassers in the network. The deterrence design by trust evaluation mechanism in combination with a clustering method is proficiently made use for the identification of the attacker and reduction of the price concerning detection method. The suggested system optimizes the utilization of a bandwidth without compromising the security of the nodes in the network.